A79 FECAL SHORT CHAIN FATTY ACID COMPOSITION IN CROHN’S DISEASE PATIENTS CONSUMING A DIVERSIFIED COMPARED TO NON-DIVERSIFIED DIET - Raman, M (J Can Assoc Gastroenterol, 2018)
BACKGROUND: Patients with Crohn’s Disease (CD) are at increased risk of nutritional deficiencies that are multifactorial in etiology, and may include poor dietary diversity. Short chain fatty acids (SCFA) are known to have anti-inflammatory properties. Nutrition status and dietary diversity have been shown to impact the gut microbiome, however the effect of dietary diversity on fecal SCFA composition in CD is understudied. AIMS: (1) To describe the baseline fecal SCFA profiles in patients with CD in remission who consume a diversified diet (DD) compared to patients who consume a non-diversified diet (NDD); (2) To describe the changes in fecal SCFA in patients with CD in remission who consume a NDD following a 3-month dietary intervention. METHODS: Patients with CD were recruited prospectively at the University of Calgary. All patients were in remission as confirmed by ileo-colonoscopy within 6 months of study entry and normal fecal calprotectin levels. A NDD was defined as fewer than 3 daily servings of fruits and vegetables, dietary fiber ≤ 15g/day, red meat intake ≥ 3 weekly servings. Patients recorded dietary intake using a 3-day food record that was analyzed by the study Registered Dietitian. Patients consuming a NDD were provided a personalized dietary intervention by the RD for 3 months to improve dietary diversity and maintained weekly food diaries to assess compliance. SCFA were measured in stool samples at baseline and after 3 months by gas chromatography. RESULTS: Twenty participants were recruited (14 DD, females: n=11; 6 NDD, females: n=4). Compared with the CD group consuming a DD group at baseline, CD patients consuming a NDD had lower levels of fecal propionate (µmol/ml) (1.56 ± 0.59 vs 2.35 ± 0.18; p=0.08), lower levels of iso-butyrate (0.12 ± 0.05 vs 0.24 ± 0.02; p=0.03), and iso-valeric acid (0.15 ± 0.06 vs 0.36 ± 0.04; p=0.01). Following a 3-month dietary intervention, a significant increase in fecal propionate was observed from baseline to 3-months (1.56 ± 0.59 vs. 2.06 ± 0.55; p <0.05) with trends towards increased acetate (7.46 ± 0.6 to 9.57 ± 1.2; p=0.06) and iso-butyrate (0.12 ± 0.05 to 0.25 ± 0.08; p=0.07). In the NDD group, non-significant increases in fecal acetate and propionate were observed from baseline to 3 months. CONCLUSIONS: CD patients consuming a non-diversified diet have reduced levels of fecal SCFA compared with patients consuming a more diversified diet. We have demonstrated that initiation of a structured dietary intervention to enhance dietary diversity will significantly increase fecal SCFA (propionate) levels. Clinical studies are underway to document the efficacy effects of this intervention. FUNDING AGENCIES: Broad Foundation